The effects of intranasal esketamine on on-road driving performance in patients with major depressive disorder or persistent depressive disorder. (May 2022) - Dijkstra, Francis M; van de Loo, Aurora JAE; Abdulahad, Smedra; Bosma, Else R; Hartog, Mitch; Huls, Hendrikje; Kuijper, Dianne C; de Vries, Esther; Solanki, Bhavna; Singh, Jaskaran; Aluisio, Leah; Zannikos, Peter; et al.
Background: Intranasal esketamine demonstrates rapid improvement of depressive symptoms. However, transient adverse effects (dissociation, sedation and dizziness) may occur, which could impact driving performance. Aims: To evaluate the effects of 84 mg intranasal esketamine on driving performance in unipolar major depressive disorder (MDD) or persistent depressive disorder (PDD) patients. Methods: The study consisted of two parts. Part A was a single-blind, double-dummy, randomized three-period, cross-over study to compare effects of esketamine versus placebo on next morning driving, 18 ± 2 h post-treatment. Alcohol was administered to demonstrate assay sensitivity. In Part B, same-day driving, 6 ± 0.5 hours post-treatment, was assessed during twice weekly esketamine administration for 3 weeks. Twenty-seven patients with mild-to-moderate MDD or PDD without psychotic features completed a 100 km on-the-road driving test on a public highway in normal traffic. The primary outcome was standard deviation of lateral position (SDLP; cm; weaving of car). Results: In Part A, alcohol impaired driving performance compared to placebo: Least-square means (95% CI), p -value for delta SDLP (cm) compared with placebo: (ΔSDLP = + 1.83 (1.03; 2.62), p  < 0.001), whereas esketamine did not: (ΔSDLP = −0.23 (−1.04; 0.58), p  = 0.572). In Part B, weekly driving tests showed no differences between placebo baseline SDLP and after esketamine administration over 3 weeks: Day 11: (ΔSDLP = −0.96 (−3.72; 1.81), p  = 0.493), Day 18: (ΔSDLP = −0.56 (−3.33; 2.20), p  = 0.686) and Day 25: (ΔSDLP = −1.05 (−3.82; 1.71), p  = 0.451). Conclusions: In this study, esketamine did not impair on-road driving performance the next morning following a single dose, or on same day after repeated administration.